Engineered exosomes enriched with select microRNAs amplify their therapeutic efficacy for traumatic brain injury and stroke - Chen, Liang; Xiong, Ye; Chopp, Michael; Zhang, Yanlu (Frontiers in Cellular Neuroscience, 2024)
Traumatic brain injury (TBI) and stroke stand as prominent causes of global disability and mortality. Treatment strategies for stroke and TBI are shifting from targeting neuroprotection toward cell-based neurorestorative strategy, aiming to augment endogenous brain remodeling, which holds considerable promise for the treatment of TBI and stroke. Compelling evidence underscores that the therapeutic effects of cell-based therapy are mediated by the active generation and release of exosomes from administered cells. Exosomes, endosomal derived and nano-sized extracellular vesicles, play a pivotal role in intercellular communication. Thus, we may independently employ exosomes to treat stroke and TBI. Systemic administration of mesenchymal stem cell (MSC) derived exosomes promotes neuroplasticity and neurological functional recovery in preclinical animal models of TBI and stroke. In this mini review, we describe the properties of exosomes and recent exosome-based therapies of TBI and stroke. It is noteworthy that the microRNA cargo within exosomes contributes to their therapeutic effects. Thus, we provide a brief introduction to microRNAs and insight into their key roles in mediating therapeutic effects. With the increasing knowledge of exosomes, researchers have “engineered” exosome microRNA content to amplify their therapeutic benefits. We therefore focus our discussion on the therapeutic benefits of recently employed microRNA-enriched engineered exosomes. We also discuss the current opportunities and challenges in translating exosome-based therapy to clinical applications.